Transparency, disclosure and the federal reserve - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2005)
This paper assesses the change in Federal Reserve policy introduced in 1999, with the publication of statements about the outlook for monetary policy (and later about the balance of risks) immediately after each FOMC meeting. We find that markets anticipated monetary policy decisions equally well under this new disclosure regime than before, but arrived at their expectations in different ways. Under the new regime, markets extract information from the statements, whereas before, they needed to revert to other types of Fed communication in the inter-meeting periods, and come to their own assessment of the implications of macroeconomic data releases. Taken together, these findings suggest that the Fed's new disclosure practice may indeed have improved transparency in the sense that information is now released to the markets at an earlier time and with clearer signals, but that the Fed can extract less information from observing market reactions to macroeconomic data releases.
Keywords: E43; E52; E58; G12; 330; announcements; communication; disclosure; monetary policy; transparency; Kommunikation; Zentralbank; Schätzung; USA